Aspects of Burial and Exhumation. (2nd May 2017) - Bursell, Rupert
Abstract : This article considers a number of legal questions surrounding burial and exhumation. Based on an extensive paper given at the Ecclesiastical Law Society's conference in 2015, it builds on previous work by the author in this area and examines the changes in the law brought about by recent case law.